Pengaruh Biological Asset Intensity, Growth, Leverage, Dan Tingkat Internasional Terhadap Pengungkapan Aset Biologis - Kurnia Hayati; Vanica Serly (Universitas Negeri Padang, 2020)
Data from the Central Statistics Agency shows Indonesia's agricultural growth rate in the first quarter of 2019 was only 1.81%. This growth rate decreased significantly, when compared to the first quarter of 2018 which reached 3,34%. This indicates that the condition of agriculture in Indonesia is very alarming. This study aims to see the effect of biological asset intensity, growth, leverage and international level to biological asset disclosure in agricultural companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2018. Disclosure of biological asset in this study refers to PSAK 69 with 36 items of disclosure. This type of research is quantitative. The population in this study were all agricultural companies listed on the Indonesia Stock Exchange (IDX), with a total sample of 66 samples using a purposive sampling method. The analysis was done by using multiple regression model. The results of this study indicate that: (1) The biological asset intesity has a positive and significant effect on the disclosure of biological asset, (2) Growth has a positive and significant effect on the disclosure of biological asset, (3) Leverage has a negative and not significant effect on the disclosure of biological asset, (4) The international level has a negative and not significant effect on the disclosure of biological asset